(untitled) (Aporia, 2024)
In “A Puzzle About Belief” (1979), Saul Kripke posits a thought experiment involving a bilingual named Pierre, who comes to what seem like contradictory beliefs about the city of London. On a popular reading, the upshot of how Kripke sets up Pierre’s problem is that the challenges of ascribing propositional attitudes such as belief to another person are more complex than suggested in previous philosophical analyses, particularly Gottlob Frege’s “Sense and Reference” (1948). In particular, Kripke aims to show that a genuine paradox about belief ascription can arise without the need to presuppose that a thinker with different beliefs about the same object relates to that object through different cognitive perspectives (i.e., what Frege called modes of presentation). In this essay, I take issue with how Kripke draws his conclusion that Pierre’s problem must go beyond Frege’s notions of sense and reference. I argue that application of Fregean notions of sense indeed ‘solves’ Kripke’s puzzle about Pierre and that Kripke’s pre-emptive reply to such an objection does not suffice, casting doubt only on how the Pierre paradox gets off the ground. In sum, I argue that a charitable understanding of Frege’s ideas and a closer interrogation of Kripke’s set-up reveals that Pierre’s ‘puzzle’ is not necessarily a puzzle.